REALIZATION OF THE PHENOMENON OF A DUAL CAREER IN THE CONDITIONS OF INTEGRATION OF SPORTS, EDUCATIONAL AND SCIENTIFIC ACTIVITIES IN UNIVERSITIES OF PHYSICAL CULTURE ORIENTATION - Petrov S.I. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the conditions for the effective implementation of a dual career for student-athletes in the course of integrating sports training into the activities of universities of physical education. Methods and structure of the study. As research methods, the theoretical analysis and generalization of special literature on the problem under study, the analysis of the content and structure of methodological support in the areas of training implemented in universities of physical education were used. Results and conclusions. Reducing the negative effects of the implementation of a dual career is possible with the right choice of the direction of higher education, with the assignment of the appropriate qualification. The most acceptable areas of training for the successful implementation of a dual career path for a student-athlete include areas UGSN (enlarged group of specialties and areas of training) 49.00.00 and the qualification “Coach by sport. Teacher". One of the prerequisites for successful integration into the educational process is the generalization of the social, psychological and professional characteristics of the trainer-teacher, reflected in the professiogram.